Swedish Forestry and its Biological Background - Singh, T. C. M.; Tewari, D. N. (Indian Forester, 1967)
Sweden's total forest resources are at present assesaed at 1,819,600,000 cubic metres, solid measures of which some 40% is represented by pine, 45% by spruce, 12% by birch and the remainder by other kinds of timber. The main objective of Swedish forestry is to deliver raw material for a continuously increasing forest industry based on export. Of tbe roundwood removals only 8% is fuelwood and about 2% used as unprocessed wood. Thus 90% of the yield goes to the industries, mainly saw mills, pulp and paper mills and fibre board factories and this part is still increasing, as the fuelwood continues to decline. Private forest-owners well as the state are fully alive to the importance of rational forestry for the national economy, and everything connected with the care and improvement of forests has received the best attention during the last few decade.